Disability representation and portrayal in selected South African soap operas: a content analysis - Swarts, Elsonia (Division of Disability Studies, 2021)
The absence of or stereotypical portrayal of persons with disabilities in the mainstream media has negative and far-reaching consequences not only for an identity of disability but for how non-disabled persons relate to persons with disabilities. Conversely, positive media portrayal and representation has the potential to challenge stereotypes and spread counter-narratives on a wide scale. This study was motivated by a perceived dearth of research into the representation of persons with disabilities in soap operas, which has been studied minimally in South Africa. The goal of the study is to contribute towards an understanding of media representation of disability and its implications in South Africa, specifically through soap opera, by investigating how South African television soap operas represent and portray disability and disability issues daily to their viewers. Drawing on relevant disability identity theory, this study used a qualitative content case study analysis of portrayal and representation of disability in two South African local soap operas, namely 7de Laan and Generations: The Legacy. These soap operas are popular among South African television audiences. The soap opera content was interpreted using qualitative content analysis by exploring the implicit and explicit representation of disability in the soap opera scenes and episodes. Contrary to the historical representation of persons with disabilities, the data revealed that persons with actual disabilities were used in the soap operas as opposed to non-disabled persons acting as if they had a disability. This positively gives a voice to persons with disabilities. However, the scenes and episodes where these characters appear are minimal and short in duration, diminishing any positive intent envisioned by including these characters in the first place. In addition, the themes that emerged from the study indicate a positive representation of persons with disabilities as contributors to the economy through their participation in work and business. At the same time, the stereotypical portrayal of ‘super cripple' in the same scenes shows how the positive representation can be rendered futile with a negative one in the same episode or scene, highlighting the importance and necessity of engaging with media representations on how they may impact individuals with disabilities in a very diverse society like South Africa.